THE DEVELOPMENT OF DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS’ SCIENCE LITERACY FOR XI GRADE STUDENTS OF SMK-SPP NEGERI SAMARINDA - Rosdiana, Rosdiana; Boleng, Didimus Tanah; Susilo, Susilo (Unnes Science Education Journal, 2017)
This research was proposed on the problems of: a) the learning process of biology which lack integration to context, knowledge, competence, and scientific behavior. It affects students’ learning outcome, where 59.6 % still did not pass the passing grade. b) lack of students’ activeness in the learning process. In fact, not all students give questions in the learning process. Students were also unable to identify and know the key concepts of the materials. And c) teacher had difficulty and limited time to develop the learning process. This research aimed to produce valid and effective learning tools based on discovery learning. It referred to the stage of research of 4D, by Thiagarajan (1974) consisted of Define, Design, Develop, and Disseminate. The made products were the syllabus, lesson plan, handout, students’ worksheet, and scoring instrument. From the research, it can be concluded that the tools were valid with the average score of 87.49 %. It was considered as very practice with positive responses of students in 84.33 %. Discovery learning model integrated with science literacy can improve the effectiveness of learning process based on the value of Normalized gain (N-gain) in the experiment class in 0.74 (high) while the control class got 0.30 (medium).